2018
DOI: 10.1186/s12887-018-1332-3
|View full text |Cite
|
Sign up to set email alerts
|

High rate of antibiotic resistance among pneumococci carried by healthy children in the eastern part of the Democratic Republic of the Congo

Abstract: BackgroundPneumococcal conjugate vaccines have been introduced in the infant immunisation programmes in many countries to reduce the rate of fatal pneumococcal infections. In the Democratic Republic of the Congo (DR Congo) a 13-valent vaccine (PCV13) was introduced in 2013. Data on the burden of circulating pneumococci among children after this introduction are lacking. In this study, we aimed to determine the risk factors related to pneumococcal carriage in healthy Congolese children after the vaccine introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
29
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 51 publications
(68 reference statements)
18
29
2
Order By: Relevance
“…Fifteen years ago, it was found that trimethoprim-sulfamethoxazole and amoxicillin were frequently used in self-medication in Congolese children having cough with or without fever [5]. We have recently showed a high level of resistance against trimethoprim-sulfamethoxazole in pneumococci colonizing healthy children in this area of DR Congo [18] and similar results were shown for healthy children in northern Tanzania [37]. Here we found that pre-hospitalisation medication by the peroral broad spectrum antibiotic trimethoprimsulfamethoxazole was more common in children with severe pneumonia than in children with nonsevere disease, and pre-hospitalisation treatment with trimethoprim-sulfamethoxazole was also associated with fatal outcome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifteen years ago, it was found that trimethoprim-sulfamethoxazole and amoxicillin were frequently used in self-medication in Congolese children having cough with or without fever [5]. We have recently showed a high level of resistance against trimethoprim-sulfamethoxazole in pneumococci colonizing healthy children in this area of DR Congo [18] and similar results were shown for healthy children in northern Tanzania [37]. Here we found that pre-hospitalisation medication by the peroral broad spectrum antibiotic trimethoprimsulfamethoxazole was more common in children with severe pneumonia than in children with nonsevere disease, and pre-hospitalisation treatment with trimethoprim-sulfamethoxazole was also associated with fatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A nasopharyngeal specimen was obtained from all included children using an Eswab (Copan Diagnostics Inc., Murrieta, CA), following a standardised procedure as previously described [18]. The samples were shipped immediately to the Clinical Laboratory at Panzi Hospital for subsequent pneumococcal culture as described earlier [18].…”
Section: Nasopharyngeal Specimen Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, the detection of 40 different serotypes was performed using a multiplex real-time PCR protocol published by the US Centers for Disease Control and Prevention (CDC) with slight modifications, as described previously (Birindwa et al, 2018). For cpsA-positive samples in which the serotype could not be detected by the multiplex PCR, the serotypes/serogroups were determined using a modified Sequetyping protocol (Birindwa et al, 2018). Briefly, two PCR reactions were set up to amplify the whole cpsB gene.…”
Section: Serotyping Of S Pneumoniaementioning
confidence: 99%